Pengembangan Kecerdasan Emosional Siswa di Sekolah Dasar Melalui Penanaman Pendidikan Karakter - Kadek Ari Wisudayanti (Edukasi: Jurnal Pendidikan Dasar, 2020)
Education is a process of humanization (humanizing humans). This means that education should be able to help students to achieve physical and spiritual maturity and maturity. Character education must be carried out continuously, internalized character values in every lesson content learned by students, character values cannot be captured by students or just taught but students must learn by themselves (students are actively involved in the process learning) and the process of implementing character education must involve students actively. Emotional intelligence is a social intelligence that is related to a person's ability to know their own emotions well and those of others and their ability to distinguish their emotions from others, where this ability is used to regulate their thought patterns and behavior.  Keywords: Emotional Intelligence and Character Education